Relationship between the Utilization of Maternal and Child Health Books and Compliance with Antenatal Care (ANC) Visits in Pregnant Women at the Tanjung Tiram Batu Bara Health Center - Irma Nurianti; Nur Azlina Akrom (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2025)
and child health. The KIA book is useful in providing information and guidance for mothers and children. In addition, the KIA book plays a role in monitoring fetal development during pregnancy, so that more effective referrals can be obtained. ANC examination is an examination carried out during pregnancy to ensure the health of the mother and fetus. The aim is to detect early potential dangers that may occur to the mother and fetus and to improve the physical and mental health of pregnant women. The examination is processed periodically with a minimum of six times during pregnancy. The type of research uses a quantitative research design in the form of an observational analytical survey through a cross-sectional approach which aims to identify the Relationship between the Utilization of the KIA Book and Compliance with ANC Visits of Pregnant Women. The number of samples was 32 pregnant women in the third trimester who were determined by total sampling. The results prove that most respondents do not utilize the KIA book so that they are less compliant in making ANC visits. In addition, the p value of 0.011 means that there is a close relationship between the utilization of the KIA book and the compliance of pregnant women in attending ANC visits. It is necessary to increase the interest of pregnant women to always use the KIA book correctly so that they will routinely comply with attending ANC visits and can improve the health of mothers and babies.